Análise da influência dos polimorfismos rs2228570 e rs1544410 do gene vdr na ocorrência de fissuras labiopalatinas não sindrômicas - Dantas, Vanessa de Melo Cavalcanti (2017)
The cleft lip and palate can be classified according to the affected structures in CL, CP or CLP (combination of both), can be classified into syndromic or non-syndromic fissures, presenting several risk factors. Vitamin D is considered a steroid hormone of great importance because it is involved in fundamental physiological processes. Vitamin D insufficiency is associated with several complications in pregnancy including pre-eclampsia and premature birth, suggesting an important role of this vitamin in maintaining pregnancy and fetal development. The VDR gene is located on the long arm of chromosome 12 and more than 470 polymorphisms were identified in the human VDR gene, among them rs2228570 and rs1544410. The objective of this work was to determine the allelic and genotypic frequencies and the associations of rs2228570 and rs1544410 with the susceptibility for the development of CL/P and CP. A control case study was used, involving 127 double tests of patients attended by the Lauro Wanderley University Hospital, being 74 CL/P and 53 CP with their respective mothers, and 82 healthy doublets attended at the Hospital Cândida Vargas. Genomic DNA from children and mothers was obtained from oral mucosal cells. The genotypes were identified by the Restriction Fragment Length technique (PCR-RFLP) and analyzed using the chi-square test. The difference of the mean age of the mothers presented difference between the control group and the CP group. The percentage of fissured children who presented a family history of clefts compared to control presented significance (p = 0.0001). The genotypic distribution and allelic frequency of rs2228570 in mothers groups and the affected groups was not different from the control group. For the rs1544410 polymorphism the comparison between the children of the CP and control groups showed a significant difference in the genotypic distribution (p = 0.017) and allele frequency presented (p = 0.008) with a predominance of the b allele in the FP group. No significant differences were found for genotypes and allelic frequency of rs1544410 in the mother group. The results of this study suggest that the b allele of rs1544410 may act as a risk factor for development and that the BB genotype may act as a protective factor for CP.